Exoneration Clausula in Due to The Marriage Agreement Made By Notary After The Decision of The Constitutional Court Number 69 / PUU-XIII-2015 - Binar Kikis Kiani (Authentica, 2021)
Arrangements regarding marital agreements after the issuance of a constitutional court ruling shifts the arrangement of when the marriage agreement may be made. Before the issuance of the Constitutional Court's ruling a marriage agreement is made before or during a marriage while after the issuance of the Constitutional Court's decision a marriage agreement may be made before, during or during marriage. This has different consequences for both, especially for the deed containing the Exoneration clause in it. This research is a Normative Juridical research which uses the statutory approach and case approach. The research specifications used are prescriptive. The author uses secondary data and the method of presenting data using narrative text forms and analyzed with qualitative juridical methods. The research results show that the exoneration clause was found in the deed made by the Notary Public before the decision of the Constitutional Court, namely the deed xx / yy in Article 4 and in the notary deed after the Constitutional Court's decision number 5 of 2019 in Article 1 and Article 2. legal consequences arising from there is an exoneration clause on the deed made before the Constitutional Court Decision, namely that the deed is null and void, but the parties may submit a remake of the marriage agreement to the notary and the Notary will make a new deed on the premises and substance while the legal consequences arising from the exoneration clause in the deed made after the Constitutional Court Decision, if the parties do not make changes to the exoneration clause, then the deed is null and void, but if it will make changes to the deed contained in the exoneration clause, the parties can submit changes to the Notary and Notary only change the substance. Suggestion from this research is the need for the role of the Notary in terms of making the agreement so that the agreement that has been stated in the deed and agreed by the parties does not harm both parties and does not cause a lawsuit in the future. Keywords: Exoneration Clause, Marriage Agreement, Constitutional Court